2021
DOI: 10.1038/s41598-021-93967-2
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning for distinguishing normal versus abnormal chest radiographs and generalization to two unseen diseases tuberculosis and COVID-19

Abstract: Chest radiography (CXR) is the most widely-used thoracic clinical imaging modality and is crucial for guiding the management of cardiothoracic conditions. The detection of specific CXR findings has been the main focus of several artificial intelligence (AI) systems. However, the wide range of possible CXR abnormalities makes it impractical to detect every possible condition by building multiple separate systems, each of which detects one or more pre-specified conditions. In this work, we developed and evaluate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 35 publications
2
29
0
Order By: Relevance
“…Although we did not compare the performance with other models in the literature, the AUCs from of our AI algorithm was similar to those reported for other models assessed with open access CXR datasets (https://nihcc.app.box.com/v/ChestXray-NIHCC/file/220660789610) (20). Apart from detection of radiographic findings assessed in our study with an AI algorithm, other studies have also assessed applications of AI for prioritizing interpretation of CXRs to expedite reporting of abnormal CXRs and specific findings (21). Baltruschat et.…”
Section: Discussionsupporting
confidence: 79%
“…Although we did not compare the performance with other models in the literature, the AUCs from of our AI algorithm was similar to those reported for other models assessed with open access CXR datasets (https://nihcc.app.box.com/v/ChestXray-NIHCC/file/220660789610) (20). Apart from detection of radiographic findings assessed in our study with an AI algorithm, other studies have also assessed applications of AI for prioritizing interpretation of CXRs to expedite reporting of abnormal CXRs and specific findings (21). Baltruschat et.…”
Section: Discussionsupporting
confidence: 79%
“…Apart from detection of radiographic findings assessed in our study with an AI algorithm, other studies have assessed applications of AI for prioritizing interpretation of CXRs in order to expedite reporting of abnormal CXRs and specific findings [ 26 ]. Baltruschat et al reported the use of AI-based worklist prioritization for a substantial reduction in reporting turnaround time for critical CXR findings [ 27 ]. Similar improvements in reporting time with worklist prioritization using AI have been reported for other body regions as well, such as head CTs for intracranial hemorrhage [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, it is expected that many of the labels assigned are incorrect. In some other studies of these data, expert labels are solicited for 810 selected testing images from multiple experienced radiologists [25].…”
Section: Estimating and Correcting Prediction Errorsmentioning
confidence: 99%